DEVELOPMENT OF AN ANDROID APPLICATION-BASED ACADEMIC INFORMATION SYSTEM AT IMMIGRATION POLYTECHNIC - Galuh Boy Hertantyo; Wahyu Eka Putra; Muhammad Wildan Bayu Fahrizal (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The Academic Information System or commonly called SIAKAD is a system created to provide easy services for students in online administrative activities. This system was built to assist the Immigration Polytechnic academics, lecturers and students in finding out information related to the academics of students and as a database of student information and cumulative grade point scores. Currently the Academic Information System (SIAKAD) is still a website-based system. The features on the website are also quite adequate. However, with current technological developments, students more often access learning media through applications than websites, which causes the Immigration Polytechnic's academic information system to be developed into an android-based application. The purpose of this research is to develop and build an Academic Information System (SIAKAD) application using Android Studio software. The research method used is the Waterfall system development method. The research results obtained are how to develop this academic information system into an android-based application, and the flow of using the Immigration Polytechnic academic information system application, as well as an android- based application product that has gone through the trial stage. The target of this android version of the SIAKAD application is to be used by students in accessing academic information online through the mobile application. Recommendations that can be given are to carry out regular maintenance and evaluation as well as carry out further development related to other operating systems as well as from the interface of applications that have been made.